Effect of resveratrol on dipeptidyl peptidase-4 inhibitors pharmacokinetics: An in vitro and in vivo approach. (5th January 2020) - Surendran, Shruti; Sapkal, Rekha; Paul, David; Nanjappan, Satheeshkumar
Abstract: Diabetes mellitus (DM) is a metabolic disorder with hyperglycemia being its hallmark symptom. The secondary symptom of DM is oxidative stress, which leads to the generation of free radicals. Diabetic nephropathy and neuropathy is the long-term effect of oxidative stress caused in DM, which leads to damage of kidneys and neurons respectively. Resveratrol (RES) is a phytochemical, found to be effective in the treatment of diabetic nephropathy and neuropathy. Due to its antioxidant property, it reduces the oxidative stress caused by DM. Dipeptidyl peptidase-4 (DPP-4) inhibitors are used for the treatment of type 2 DM. In vitro and in vivo data depicted that the metabolism of alogliptin (ALO), saxagliptin (SAX) and sitagliptin (SIT) were decreased in presence of RES while metabolism of teneligliptin (TEN) was not affected in presence of RES. The results show that the alteration of the pharmacokinetics of ALO, SAX and SIT was due to inhibition of CYP P450 by RES. Thus, there was a significant pharmacokinetic interaction between RES-ALO, RES-SAX and RES-SIT. Hence, a dose reduction is required when RES therapy is taken in combination with ALO, SAX and SIT as there is an increase in drug exposure, which might lead to toxicity. Graphical abstract: Image 1 Highlights: Study investigated the effect of RES on the pharmacokinetics of DPP-4 inhibitors. In vitro and in vivo data depicted that RES altered its pharmacokinetics. The pharmacokinetic parameters were evaluated using WinNonLin software. Dose adjustments are necessary when RES is co-administered.